Optimal Positive End Expiratory Pressure Levels in Ventilated Patients Without Acute Respiratory Distress Syndrome: A Bayesian Network Meta-Analysis and Systematic Review of Randomized Controlled Trials - Zhou, Jing; Lin, Zhimin; Deng, Xiumei; Liu, Baiyun; Zhang, Yu; Zheng, Yongxin; Zheng, Haichong; Wang, Yingzhi; Lai, Yan; Huang, Weixiang; Liu, Xiaoqing; He, Weiqun; et al. (Frontiers in Medicine, 2021)
Background To find the optimal positive end expiratory pressure (PEEP) in mechanical ventilated patients without Acute Respiratory Distress Syndrome (ARDS), we conducted a Bayesian network meta-analysis and systematic review of randomized controlled trials (RCTs) comparing different level of PEEP based on a novel classification of PEEP level: ZEEP group (PEEP = 0 cm H2O); lower PEEP group（PEEP=1-6cmH2O）；intermediate PEEP group (PEEP = 7-10 cm H2O）；higher PEEP group (PEEP>10cmH2O). Result 28 eligible studies with 2712 patients were included. There were no significant differences in the duration of mechanical ventilation between higher and intermediate PEEP (MD: 0.020, 95% CI: -0.14, 0.28), higher and lower PEEP (MD: -0.010, 95% CI: -0.23, 0.22), higher PEEP and ZEEP (MD: 0.010, 95% CI: -0.40, 0.22), intermediate and lower PEEP (MD: -0.040, 95% CI: -0.18, 0.040), intermediate PEEP and ZEEP (MD: -0.010, 95% CI: -0.42, 0.10), lower PEEP and ZEEP (MD: 0.020, 95% CI: -0.32, 0.13), respectively. Higher PEEP was associated with significantly higher PaO2/FiO2 ratio(PFR) when compared to ZEEP (MD: 73.24, 95% CI:11.03, 130.7), and higher incidence of pneumothorax when compared to intermediate PEEP, lower PEEP and ZEEP(OR: 2.91e+12, 95% CI:40.3, 1.76e+39; OR: 1.85e+12, 95% CI:29.2, 1.18e+39; and OR: 1.44e+12, 95% CI:16.9, 8.70e+38, respectively). There was no association between PEEP levels and other secondary outcomes. Conclusion We identified higher PEEP was associated with significantly higher PFR and higher incidence of pneumothorax. Nonetheless, in terms of other outcomes, no significant differences were detected among four levels of PEEP.